Molecular constraints of sarcopenia in the ageing muscle - Damanti, S.; Senini, E.; De Lorenzo, R.; Merolla, A.; Santoro, S.; Festorazzi, C.; Messina, M.; Vitali, G.; Sciorati, C.; Manfredi, A. A.; Rovere-Querini, P. (Frontiers in Aging, 2025)
Sarcopenia, the age-related loss of skeletal muscle mass, strength, and function, is driven by a convergence of molecular, cellular, hormonal, nutritional, and neurological alterations. Skeletal muscle comprises multinucleated fibers supported by satellite cells—muscle stem cells essential for repair and regeneration. With age, both the structure and function of these components deteriorate: myonuclei become disorganized, gene expression skews toward catabolic, inflammatory, and fibrotic pathways, and satellite cell numbers and activity decline. Concurrently, mitochondrial dysfunction, impaired proteostasis, and vascular rarefaction limit energy availability and regenerative capacity. Neurodegeneration and age-related muscle fibers denervation further exacerbate muscle loss, particularly affecting fast-twitch fibers, and reduce motor unit integrity. These neural deficits, alongside changes at the neuromuscular junction, contribute to functional decline and diminished contractility. Hormonal changes—including reduced levels of growth hormone, testosterone, and IGF-1—undermine anabolic signaling and promote muscle atrophy. Nutritional factors are also pivotal: anorexia of aging and reduced dietary protein intake lead to suboptimal nutrient availability. Compounding this is anabolic resistance, a hallmark of aging muscle, in which higher levels of dietary protein and amino acids are required to stimulate muscle protein synthesis effectively. Physical inactivity and immobility, often secondary to chronic illness or frailty, further accelerate sarcopenia by promoting disuse atrophy. The molecular constraints of sarcopenia are deeply intertwined with non-molecular mechanisms—such as neuromuscular degeneration, hormonal shifts, inadequate nutrition, and reduced physical activity—creating a complex and self-reinforcing cycle that impairs muscle maintenance and regeneration in the elderly. This review synthesizes current evidence on these interconnected factors, highlighting opportunities for targeted interventions to preserve muscle health across the lifespan.